Functionality and occupational analysis of a 3D-printed body-powered upper-limb prosthesis prototype for children and adolescents - Vanessa Wiesner Luna; Yury Arenis Olarte Arias (Ocupación Humana, 2025)
In Colombia, socio-economic barriers disproportionately limit children and adolescents’ access to prosthetic devices. The functionality and potential everyday occupational uses of a low-cost, 3D-printed body-powered upper-limb prosthesis for children and adolescents with congenital limb absence are explored. A multiple-case study was employed within a mixed-methods exploratory sequential design. Four people who had received the prosthesis six weeks earlier, without prior training, were evaluated through direct observation, the Jebsen-Taylor Hand Function Test, and the University of New Brunswick Test of Prosthetic Function. While the prosthesis improved functional grasp patterns and bimanual activity participation, task execution times were prolonged, and spontaneous use was inconsistent. Interaction with the prosthesis was mainly in gross motor tasks. The need for optimized prosthetic design and structured occupational therapy interventions, including prescription, training, and follow-up, is highlighted. The importance of integrating rehabilitation strategies with assistive technology to enhance functional independence and occupational participation in pediatric prosthesis users is emphasized.